2022
DOI: 10.1101/2022.03.08.483397
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

miR-329 and miR-495-mediated Prr7 downregulation is required for homeostatic synaptic depression in rat hippocampal neurons

Abstract: Homeostatic synaptic depression (HSD) in excitatory neurons is a cell autonomous mechanism which protects excitatory neurons from over-excitation as a consequence of chronic increases in network activity. In this process, excitatory synapses are weakened and eventually eliminated, as evidenced by a reduction in synaptic AMPA receptor expression and dendritic spine loss. Originally considered a global, cell-wide mechanism, local forms of regulation, such as the local control of mRNA translation in dendrites, ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…It has been reported that miR-329-3p and miR-495-3p induce homeostatic synaptic depression (HSD) and inhibit chronic increases in network activity. These miRNAs inhibit proline-rich protein 7/ transmembrane adapter protein 3 (Prr7) which is the protein involved in the stability of excitatory synapses and the size of dendritic spines at the synaptic site through protection of synaptic proteins (Inouye et al, 2022).…”
Section: Micrornas Are Important Regulators Of Neural Development In ...mentioning
confidence: 99%
“…It has been reported that miR-329-3p and miR-495-3p induce homeostatic synaptic depression (HSD) and inhibit chronic increases in network activity. These miRNAs inhibit proline-rich protein 7/ transmembrane adapter protein 3 (Prr7) which is the protein involved in the stability of excitatory synapses and the size of dendritic spines at the synaptic site through protection of synaptic proteins (Inouye et al, 2022).…”
Section: Micrornas Are Important Regulators Of Neural Development In ...mentioning
confidence: 99%